A stem delphinidan from the Caribbean region of Venezuela - Benites-Palomino, Aldo (Swiss J Palaeontol, 2021)
The dense Miocene record of cetaceans is known from localities along the coasts of all continents, mostly in the northern Atlantic or the eastern Pacific regions, but Antarctica. Fossils from the Caribbean region are few and include of a couple of findings from Panama and Venezuela. Here, we report a partly complete skull from the Caujarao Formation (middle Miocene), Falcon State, Caribbean region of Venezuela. Our phylogenetic analyses indicate that the Caujarao specimen is a ‘stem delphinidan’, a group that includes several taxa of early diverging odontocetes whose phylogenetic affinities remain a matter of debate. The fossil record has shown that this group of stem delphinidans was taxonomically diverse, but displayed a somewhat homogeneous cranial patterning, with most of the variations being found within the mandible or tympanoperiotic characters. As other stem delphinidans the Caujarao odontocete displays an enlarged temporal fossa and a fairly symmetrical cranium. Because the skull is missing several key diagnostic characters due to the preservation state of the specimen, a more precise taxonomic identification is not possible. Despite this, the finding of this specimen highlights the importance of the fossil record from the Neogene of Venezuela, and the importance of the area to understand cetacean evolution in the proto-Caribbean.